SAT0127 The efficacy of tofacitinib in patients with rheumatoid arthritis stratified by baseline body mass index. (12th June 2018) - Dikranian, A.; Gonzalez-Gay, M. A.; Wellborne, F.; Alvaro-Gracia, J. M.; Takiya, L.; Stockert, L.; Chapman, D.; Tatulych, S.; Dahl, P.; Curtis, J. R.
Abstract : Background: Tofacitinib is anoral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). Objectives: This post hoc analysis aims to explore the efficacy of tofacitinib in patients (pts) with RA based on their baseline (BL) body mass index (BMI). Methods: Data were analysed from six Phase 3 studies for pts who were methotrexate-naïve (NCT01039688 ) or had an inadequate response to DMARDs (NCT00960440, NCT00847613, NCT00814307, NCT00856544, NCT00853385 ) and received ≥1 dose of tofacitinib 5 or 10 mg twice daily (BID) or placebo (PBO). Pts were stratified by BL BMI (<25, 25 to <30, ≥30). Efficacy endpoints (American College of Rheumatology [ACR]20/50/70 response rates at Month [M]6; changes from baseline [Δ] in Health Assessment Questionnaire-Disability Index [HAQ-DI], Disease Activity Score in 28 joints based on Erythrocyte Sedimentation Rate [DAS28-4(ESR)], DAS28 based on C-reactive protein [DAS28-4(CRP)] and Clinical Disease Activity Index [CDAI] at M3 and M6) were assessed. Non-responder imputation was used for the binary endpoints. No imputation was used for continuous endpoints. No multiplicity adjustment was performed in this post hoc analysis. Results: Overall, 1589, 1611 and 681 pts received tofacitinib 5 and 10 mg BID and PBO, respectively, with 1690, 1173 and 1017 pts in the BMI <25, 25 to <30 and ≥30 categories, respectively. BL demographics were generally similar between BMI categories with the exception of higher rates of diabetes (12.9-14.2% vs 3.5-9.8%), hypertension (53.2-58.9% vs 22.0-39.8%), and use of prior TNFi (23.7-46.8% vs 15.0-26.9%), and numerically higher tender (28.8-29.9 vs 23.5-26.9) and swollen joint counts (16.5-17.1 vs 14.5-16.3) and HAQ-DI scores (1.6 vs 1.4-1.5) in the BMI ≥30 group vs BMI <25 or 25 to <30. ACR response rates were significantly higher (p<0.05) in the tofacitinib vs PBO groups, regardless of BMI category(figure 1). In general, there appeared to be a trend towards lower ACR20/50/70 response rates with increasing BMI at M6 in tofacitinib- and PBO-treated pts; however, confidence intervals (CI) overlapped. At M6, ΔHAQ-DI was numerically smaller for pts receiving tofacitinib 5 mg BID with BMI ≥30 vs lower BMIcategories, with overlapping CI. The ΔDAS28-4(ESR), ΔDAS28-4(CRP) and ΔCDAIscores were similar within each treatment group regardless of BL BMI. Generallysimilar trends were observed when stratified by weight. Conclusions: Results of this post hoc analysis suggest that tofacitinib is associated with improvements in RA outcomes compared with PBO regardless of BL BMI category. In both tofacitinib and PBO groups, similar trends in improvements were seen in most endpoints regardless of BMI category, implying that the effect of BL BMI is not specific to tofacitinib. Further investigation is needed to assess the degree of impactof BMI on tofacitinib efficacy. Acknowledgements: Study sponsored by Pfizer Inc. Medical writing support was provided by C Viegelmann of CMC and funded by Pfizer Inc. Disclosure of Interest: A. DikranianGrant/research support from: AbbVie, Mallinckrodt, Pfizer Inc, Speakers bureau:AbbVie, Amgen, Celgene, Mallinckrodt, Pfizer Inc, M. Gonzalez-Gay Consultant for: Pfizer Inc, F. Wellborne Grant/research support from: AbbVie, BMS, EliLilly, Novartis, Pfizer Inc, Sanofi/Genzyme/Regeneron, Consultant for: AbbVie, BMS, Novartis, Pfizer Inc, Sanofi/Genzyme/Regeneron, Speakers bureau: AbbVie, BMS, Eli Lilly, Novartis, Pfizer Inc, Sanofi/Genzyme/Regeneron, J.Alvaro-Gracia Consultant for: Abbvie, BMS, Eli Lilly, MSD, Novartis, PfizerInc, Roche, Sanofi/Genzyme/Regeneron, Speakers bureau: Abbvie, BMS, Eli Lilly, MSD, Novartis, Pfizer Inc, Roche, Sanofi/Genzyme/Regeneron, L. Takiya Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Stockert Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Chapman Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Tatulych Shareholder of: Pfizer Inc, Employee of:Pfizer Inc, P. Dahl Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J.Curtis Grant/research support from: Amgen, Corrona, Crescendo Bio, Pfizer Inc, Consultant for: AbbVie, Amgen, BMS, Corrona, Eli Lilly, Janssen, Myriad, Roche/Genentech, UCB